Analisis Analisis Kesalahan Mahasiswa dalam Menjawab Soal Barisan Cauchy berdasarkan Teori Newman - Sarah, Siti; Sulaiman, Raysah Puteri; Hutapea, Yonata; Tarigan, Septi Agita; Simanullang, Michael Christian (FKIP Universitas Mataram, 2025)
This study aims to identify the types of reading errors made by students in solving Cauchy sequence problems in a Real Analysis course. The research employed a descriptive qualitative method using Newman's theory as the analytical framework. The subjects were Mathematics Education students at Universitas Negeri Medan who had completed the course. The results revealed that students made errors in reading, understanding the problems, and performing calculation procedures, particularly in grasping the fundamental concept of Cauchy sequences. These findings highlight the need to strengthen conceptual understanding through more targeted learning strategies and the application of Newman’s theory as a tool for diagnosing errors.